FORMULATION OF MESENCHYMAL STEM CELL SECRETOME AS ANTIAGING CREAM - MARLINA; PRADIFTA, REYSA; LUCIDA, HENNY; SUDJI, IKHWAN RESMALA; SALSABILA, HANA NURUL; ELIDA, NUR; NAMIRA, POPY AYU (International Journal of Applied Pharmaceutics, 2023)
Objective: Skin aging occurs not only due to age but is influenced by various environmental factors such as lifestyle, pollution, and excessive exposure to UV rays. Secretomes can act as antiaging agents that stimulate collagen biosynthesis naturally in the skin. This study aims to create a cream containing 5% secretome with essential oil, dermatological examination, and Fibroblast Growth Factor (FGF) checking. Methods: Antiaging efficacy testing involves examination by an expert dermatologist for assessment before and after using the cream. The antiaging impact test criteria include moisture, elasticity, and collagen values. Consequently, the cream shows an antiaging activity. Results: The antiaging efficacy test revealed increased moisture from 24.375±11.97 to 25.125±7.1; the skin elasticity also increased from 40.375±8.39 to 48.5±9.09 and the collagen value increased from 48.25±13.54 to 56.5±8.63. The result shows that the cream contains a 61.143 pg/ml concentration of FGF using an ELISA kit. Conclusion: The formula for cream preparations containing 5% secretome with essential oil meets the requirements of cosmetics through several evaluations of the trial. It has an antiaging effect, proven through several tests.